LIMBSHAKING SEBAGAI MANIFESTASI YANG JARANG DARI TRANSIENT ISCHEMIC ATTACK AKIBAT STENOSIS BERAT ARTERI KAROTIS - Kumara Tini* (NEURONA, 2017)
IS A RARE MANIFESTATION OF TRANSIENT ISCHEMIC ATTACK TIA COMMONLY OCCURS WHEN A SEVERE CAROTID STENOSIS CAUSES A CEREBRAL HYPOPERFUSION